Effect of water availability and seed source on physical dormancy break of Vicia villosa ssp. villosa - Renzi Pugni, Juan Pablo; Chantre Balacca, Guillermo Ruben; Cantamutto, Miguel Angel (2018)
Physical dormancy (PY) plays a crucial role in the control of the reseeding process of Vicia villosa Roth, a winter annual species cultivated for pasture and hay, naturalized in several semi-arid temperate agroecosystems. As PY is considered a seed trait modulated by natural selection, populations from different origins are expected to show different responses to environmental regulatory factors. The present study aimed to determine the effect of: (1) water availability on PY-break dynamics of a naturalized population from Argentina (ASC) under both laboratory and field conditions; (2) the seed source on initial PY and dormancy release rate (wet storage at 20°C) of ASC compared to 45 other populations of V. villosa, including wild, naturalized, landraces and cultivars. Water availability increased PY loss rate under both storage and field conditions. ASC PY-break dynamics was adequately described by a Gompertz model with a lower thermal-time requirement estimated for dormancy break under fluctuating soil water conditions compared to seeds buried inside impermeable bags. During the field burial experiment, a considerable proportion of seeds (~70%) became water permeable during the summer season after dispersal, and retained low levels of residual PY for soil seed bank replenishment. Improved populations (i.e. breeding cultivars) showed the lowest percentages of initial PY compared to landraces, naturalized and wild populations. Naturalized populations of Argentina showed similar initial PY compared to landraces, although PY release rate was lower in the former and might be attributed to local environmental selection. Wild types showed the lowest PY release rates.